2017
DOI: 10.1080/09243453.2017.1404478
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of effective teaching

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This is in keeping with Bandura (1986) identifying the relationship between emotional states and self-efficacy beliefs, defined as a belief in one's personal capability to perform a specific function, leading to desired outcomes (Bandura, 1986). Effective teachers have high levels of self-efficacy (Steele, 2010) and positively impact student achievement (OECD, 2009;Stronge, 2010;Tymms et al, 2018). Isbell et al (2016) posit an 'affect-as-cognitivefeedback model' to explain how a person's affective state influences immediate cognitive functions and evidence from the medical sciences show the impact of emotions on such things as: decision-making, perception, interpersonal interactions and intelligence (Bulagang et al, 2020).…”
Section: Literaturementioning
confidence: 90%
“…This is in keeping with Bandura (1986) identifying the relationship between emotional states and self-efficacy beliefs, defined as a belief in one's personal capability to perform a specific function, leading to desired outcomes (Bandura, 1986). Effective teachers have high levels of self-efficacy (Steele, 2010) and positively impact student achievement (OECD, 2009;Stronge, 2010;Tymms et al, 2018). Isbell et al (2016) posit an 'affect-as-cognitivefeedback model' to explain how a person's affective state influences immediate cognitive functions and evidence from the medical sciences show the impact of emotions on such things as: decision-making, perception, interpersonal interactions and intelligence (Bulagang et al, 2020).…”
Section: Literaturementioning
confidence: 90%
“…Teachers bear a high responsibility for the cognitive and psychosocial development of students, and their work performance, in terms of instructional quality, is highly relevant for students’ outcomes (Hamre & Pianta, 2001; Kunter et al, 2013; Nye et al, 2004; Tymms et al, 2018). At the same time, empirical evidence from different countries and education systems has shown that teachers are likely to be at risk for burnout symptoms such as emotional exhaustion (Iriarte Redín & Erro-Garcés, 2020; Maslach et al, 2001).…”
Section: Emotional Exhaustion and Its Work-related Consequences: A Th...mentioning
confidence: 99%
“…In this sense, peer tutoring interventions are also expected to have a positive impact on students' attitudes towards learning. As Tymms et al (2018) and Topping (2022) indicate, peers may play a vital role on other students' attitudes in class. So, structured and supervised helping behaviours in educational contexts may foster students' attitudes towards learning.…”
Section: Anxiety Attitudes and Self-concept In Peer Tutoringmentioning
confidence: 99%